Treatment Outcomes Following Resident Performed Nonvalved (Baerveldt 350) Glaucoma Drainage Device Implantation. Issue 11 (November 2019) - Rothman, Adam L.; Rosdahl, Jullia A.; Hunter, Thomas G.; Challa, Pratap; Muir, Kelly W.
Abstract : Precis: When compared with outcomes by glaucoma specialists in several prospective studies, residents at the Durham Veterans Affairs Medical Center achieved comparable reductions in intraocular pressure (IOP) and failure rates during the year following Baerveldt drainage device implantation. Purpose: To review the outcomes of resident performed Baerveldt implantation through 1 year of postoperative management in a resident-run clinic. Materials and Methods: The medical records of all veterans at the Durham Veterans Affairs Medical Center were searched to identify those with Baerveldt implantation by resident physicians from July 1, 2007 to June 30, 2017. Exclusion criteria include previous glaucoma tube or concurrent surgical intervention, including cataract extraction. All postoperative visits were reviewed and clinical data were collected. Failure was defined as 2 consecutive visits, starting at postoperative month (POM) 3, with IOP ⩽5 mm Hg, or with IOP >21 mm Hg or <20% IOP reduction from baseline, reoperation for glaucoma, or loss of light perception. Results: A total of 48 eyes were included with mean (SD) IOP and number of medications: baseline, 23.1 (6.7) mm Hg on 3.7 (1.0) medications; postoperative day 1, 20.5 (11.7) mm Hg on no medications; postoperative week 1, 14.3 (6.9) mm Hg and 1.9 (1.7) medications; POM1, 16.7 (6.4) mm Hg and 2.2 (1.5) medications; POM3, 15.1 (5.2) mm Hg and 2.1 (1.6) medications; POM6 12.8 (4.9) mm Hg and 2.8 (1.3) medications; POM12, 13.0 (4.0) mm Hg and 2.8 (1.4) medications. IOP decreased at all time intervals ( P <0.01) but postoperative day 1 ( P =0.15) while medication burden was reduced at every visit ( P <0.01). Through 12 months, 8 patients (17%) failed with a time to failure of 9.2 (0.3) months. No patients underwent additional glaucoma surgical interventions or lost light perception. Conclusions: Residents can safely and efficaciously perform Baerveldt implantation, providing reassurance regarding the autonomy afforded residents in the operating room and clinic. Abstract : Supplemental Digital Content is available in the text.